4 - Scientific Content Creation and Dissemination: Opportunities for African Universities in Electronic Publishing - Elisha R.T. Chiware (Africa Media Review, 2007)
Africa has made some strides in accessing the Internet over the last decade or so and it has managed to upload considerable information on to the Internet in the areas of business, information technology, connectivity and politics. But there is a missing link in scientific and technological information content creation and dissemination. Several proposals have been made to narrow the gap between developed countries and Africa in terms of uploading information on to the Internet. Besides the growing public information and the presence of commercial web, content generated from African universities is expanding. Internet connectivity in Africa and most of the developing world initially took root mainly in academic institutions and among academics. In some parts of Africa, universities were pioneer users of e-mail and Internet access and there is very little evidence that their interest in ICTs has waned; rather, it is growing. Most African universities with full Internet connectivity have the potential of playing a critical role in content creation and dissemination through electronic publishing because of their research interests. This paper will address the problems that Africa currently faces in developing content for the Internet and in disseminating that information. The paper will look at institutions that have the potential for creating content for the Internet. It will focus mainly on universities and research institutions’ capacities to take on this role. The paper also addresses other issues of access like limited bandwidth, unreliable electricity and communication transmission services, lack of technical expertise, high costs, etc.